Neural Stem Cells Restore Hair Growth through Activation of the Hair Follicle Niche - Insik Hwang (Cell Transplantation, 2016)
Several types of hair loss result from the inability of hair follicles to initiate the anagen phase of the hair regeneration cycle. Modulating signaling pathways in the hair follicle niche can stimulate entry into the anagen phase. Despite much effort, stem cell-based or pharmacological therapies to activate the hair follicle niche have not been successful. Here, we set out to test the effect of neural stem cell (NSC) extract on the hair follicle niche for hair regrowth. NSC extracts were applied to the immortalized cell lines HaCaT keratinocytes and dermal papilla cells (DPCs) and the shaven dorsal skin of mice. Treatment with NSC extract dramatically improved the growth of HaCaT keratinocytes and DPCs. In addition, NSC extract enhanced the hair growth of the shaven dorsal skin of mice. In order to determine the molecular signaling pathways regulated by NSCs, we evaluated the expression levels of multiple growth and signaling factors, such as insulin-like growth factor-1 (IGF-1), hepatocyte growth factor (HGF), keratinocyte growth factor (KGF), vascular endothelial growth factor (VEGF), transforming growth factor-β (TGF-β), and bone morphogenetic protein (BMP) family members. We found that treatment with an NSC extract enhanced hair growth by activating hair follicle niches via coregulation of TGF-β and BMP signaling pathways in the telogen phase. We also observed activation and differentiation of intrafollicular hair follicle stem cells, matrix cells, and extrafollicular DPCs in vivo and in vitro. We tested whether activation of growth factor pathways is a major effect of NSC treatment on hair growth by applying the growth factors to mouse skin. Combined growth factors, including TGF-β, significantly increased the hair shaft length and growth rate. DNA damage and cell death were not observed in skin cells of mice treated with the NSC extract for a prolonged period. Overall, our data demonstrate that NSC extract provides an effective approach for promoting hair growth by directly regulating hair follicle niches through TGF-β and BMP signaling pathways as well as induction of core growth factors.